Ultrasound‐guided lower forearm median nerve block in open surgery for trigger thumb in 1‐ to 3‐year‐old children: A randomized trial. Issue 2 (5th December 2017) - Liu, Wei; Liu, Jianxia; Tan, Xingqin; Wang, Shouyong
Summary: Background and Aim: Trigger thumb is a common hand disability in children and is primarily treated with open surgery. A conscious median nerve block can usually meet the requirements for trigger thumb‐releasing surgery in adults; however, its effectiveness in children requires further clarification. The present study aims to demonstrate whether ultrasound‐guided lower forearm median nerve blockade is a viable option for children undergoing open surgery for trigger thumb. Methods: A prospective randomized study was designed to compare median nerve blocks guided by ultrasonography with those guided by anatomic landmarks. Following induction of general anesthesia, the children received a median nerve block performed either by ultrasound‐guided block of the lower forearm (group U) or landmark‐based blocking at the proximal wrist crease level (group T) with a 0.2% ropivacaine injection. The success rates were compared between groups as the primary endpoint; additional sufentanil and propofol administration, anesthesia recovery time, and other secondary endpoints were also compared. Results: A total of 100 children (age 1‐3 years) with ASA status I who were scheduled for open surgery for trigger thumb were included in this study (n = 50 per group). Thirty‐seven children in group T and 50 children in group U underwent successful blocks. The rate of unsuccessful blockade was significantly lower in group U than group T (0% and 26%, respectively), and rate of additional sufentanil and propofol administration was also lower in group U than in group T. Conclusion: Ultrasound‐guided lower forearm median nerve block can provide more effective analgesia, a higher success rate, and lower general and local anesthetic dosages than the anatomic landmark‐based blocking method in children undergoing open surgery for trigger thumb.